2018
DOI: 10.1186/s12885-018-5072-4
|View full text |Cite
|
Sign up to set email alerts
|

CDCA5 overexpression is an Indicator of poor prognosis in patients with hepatocellular carcinoma (HCC)

Abstract: BackgroundAccurate and early prognosis of disease is essential to clinical decision making, particularly in diseases, such as HCC, that are typically diagnosed at a late stage in the course of disease and therefore carry a poor prognosis. CDCA5 is a cell cycle regulatory protein that has shown prognostic value in several cancers.MethodsWe retrospectively evaluated 178 patients with HCC treated with curative liver resection between September 2009 and September 2012 at Nanchong Central Hospital in Nanchong, Sich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…Cell division cycle-associated 5 (CDCA5) serves an important role in promoting colorectal cancer progression by activating the ERK signaling pathway (Shen et al, 2019). Additionally, CDCA5 could be associated with HCC (Tian et al, 2018), breast cancer (Phan et al, 2018), and lung carcinogenesis (Nguyen et al, 2010). Centromere protein U (CENPU) promotes nonsmall cell lung cancer proliferation involving the Wnt/b-catenin signaling pathway and predicts poor survival through the expression of FOXM1 (Wang et al, 2018;Zhang et al, 2018).…”
Section: Identification Of Targeted Genes In Hcc 773mentioning
confidence: 99%
“…Cell division cycle-associated 5 (CDCA5) serves an important role in promoting colorectal cancer progression by activating the ERK signaling pathway (Shen et al, 2019). Additionally, CDCA5 could be associated with HCC (Tian et al, 2018), breast cancer (Phan et al, 2018), and lung carcinogenesis (Nguyen et al, 2010). Centromere protein U (CENPU) promotes nonsmall cell lung cancer proliferation involving the Wnt/b-catenin signaling pathway and predicts poor survival through the expression of FOXM1 (Wang et al, 2018;Zhang et al, 2018).…”
Section: Identification Of Targeted Genes In Hcc 773mentioning
confidence: 99%
“…Besides, CDCA5 was found to be transcribed by E2F1, and could promote oncogenesis by enhancing cell proliferation and inhibiting apoptosis via the AKT pathway in HCC [18]. Another research found that increased CDCA5 expression was associated with increased tumor diameter and microvascular invasion in HCC [19]. Furthermore, silencing of CDCA5 inhibited cell proliferation and induced G2/M cycle arrest in vitro, and CDCA5 down-regulation in xenograft model impeded HCC growth in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…In order to explore the specific mechanism of the effect of these genes on survival, we screened the top 10 genes (CDC20, NCAPH, CDCA5, BUB1, CDCA8, PBK, KIF2C, TPX2, TTK and TOP2A). By retrieving related literature, we found that CDCA5 and CDCA8, as important regulatory proteins in the cell cycle in cancer, were recognized as oncogenes [26][27][28][29]. However, compared with other genes, there scarcely no reports about the mechanism of CDCA5 and CDCA8 with GBM.…”
Section: Discussionmentioning
confidence: 99%